Phytochemical Screening and Antimicrobial Activity of Bundung Plants Extract by Dilution Method - Noval Noval; Iwan Yuwindry; Dahlia Syahrina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Bundung plants (Actinuscirpus Grossus) are widely spread in Borneo and used by society empirically as antimicrobials. Nevertheless, the use of Bundung plants as traditional medicine has not been equipped with convincing data, because there is no research that is related to the plants. In order to the use of the plants accountable, it is necessary to conduct research about phytochemical screening studies and tests the antimicrobial activity of ethanol extract of Bundung plants to staphylococcus aureusandEschericia Coli bacteria. Moreover, extraction does with maceration method. Secondary metabolite groups which are contained in the ethanol extract of Bundung plants were determined qualitatively using several of phytochemical reagents. The result of phytochemical screening test showed that ethanol extract of Bundung plants contains a group of secondary metabolites; namely flavonoid, tannin, saponin, phenolic, steroid and terpenoid. The method that was used to test antimicrobial activity to Staphylococcus aureusandEschericia Coli bacteria was a liquid dilution method with variations in extract concentration of 0,5%, 1%, 2%, 4% and 8% by considering at the clarity of each sample. The result of antimicrobial activity of liquid dilution to bacteria had inhibition at all concentrations and the biggest inhibitory activity was shown at concentration 8% with the clearest level and the MIC grade of the test is at a concentration of 1%. Based on the findings, it can be concluded that ethanol extract of Bundung plants has the potential of activities of an antimicrobial, especially from secondary flavonoid metabolites.